Climatic Change and Groundwater: India?s Opportunities for Mitigation and Adaptation - Shah, Tushaar (2009)
For millennia, India has been using surface storages and gravity flow to irrigate its crops. During the last 40 years, however, India has witnessed a decline in gravity flow irrigation and the rise of a booming ?water-scavenging? irrigation economy through millions of small, private tube wells. For India, groundwater has become at once critical and threatened. Climatic change will act as a force-multiplier; it will enhance the criticality of groundwater for drought-proofing agriculture and simultaneously multiply the threat to the resource. Groundwater pumping with electricity and diesel also accounts for an estimated 16-25 million tonnes of carbon emission, 4-6% of the country?s total emission. From the point of view of climatic change, India?s groundwater hot spots are western and Peninsular India. These are critical for mitigation of, and adaptation to, climatic change. To achieve both, India needs to make a transition from surface storages to ?managed aquifer storage? as the comerstone of its water strategy with proactive demand and supply-side management components. In doing this, India needs to learn intelligently from the experience of countries like Australia and the USA that have long experience in managed aquifer recharge.